Diagnostic yield of electromagnetic navigational bronchoscopy: results of initial 35 cases in a Japanese institute - Sato, Toshihiko (J Thorac Dis, 2018)
BACKGROUND: Electromagnetic navigational bronchoscopy (ENB) is a new bronchoscopic technique for navigational transbronchial lung biopsy (TBLB) that guides the sheath to the target lesion in real time. Herein, we report our experience with this navigational system, its diagnostic yields, and associated complications. METHODS: A single-center, single-operator retrospective chart review was performed. We included 35 consecutive patients who underwent ENB with superDimension(TM) (Medtronic, MN, USA) for the diagnosis of pulmonary lesions from February 2016 to May 2017 in Kyoto University Hospital. The size of the target lesion varied from 8 to 25 mm (median, 15.28±5.48 mm). All ENB procedures were performed under conscious sedation using 2 to 10 mg midazolam and 1 to 10 mg morphine hydrochloride. No fluoroscopic guide was employed except in three cases. RESULTS: A total of 25 patients were diagnosed via ENB, yielding a diagnostic rate of 71.4% (25/35). The average lesion size of the diagnosed group was 16.44±5.44 mm (range, 8–25 mm). Eighteen cases were diagnosed as primary lung cancer, 3 were metastatic lung cancer, and 4 were inflammatory diseases. The average lesion size of the 10 undiagnosed cases was 12.40±5.21 mm (range, 8–24 mm). The lesion size of the undiagnosed group was significantly smaller than that of the diagnosed group (P=0.02). The average time required for the procedure was 16.78±9.57 minutes (range, 3–46 minutes), independent of the diagnosis, the lesion size, and the tumor location. We encountered one pneumothorax which required chest drainage and one hemopneumothorax which required non-elective thoracotomy and wedge resection. One patient developed high fever over 38 °C for one day following the procedure. CONCLUSIONS: In our initial series of 35 cases, ENB-guided TBLB showed an acceptable diagnostic yield.